The Plasticing Effect on Structure Forming and Crystallization Processes in Polymer Blends of Polypropylene-Poly(Vinyl Alcohol) - L. S. Dzubenko; V. P. Plavan; N. M. Rezanova; O. I. Orans’ka; O. O. Sapyanenko; P. P. Gorbyk (Фізика і хімія твердого тіла, 2018)
There is one established, that glycerol’s injection in (7,0 ÷ 15,0) % of mass. amount into polymer blend of polypropylene/poly(vinyl alcohol) (PP/PVA) of mass equation 30/70 % is not changing the structure forming character of PP into PVA matrix: there are parts, films and external shells being formed alongside with PP fibers. When at this, during concentration increase of selective plastifier, there are PP fiber forming process into PP matrix gonna being bad, and those are consisting in average microfiber diameters and mass part of films increase. There are features of structure forming, being linked in plastifying effect of glycerol on the blend melts, and, when simultaneously with, in the those decrease of kinetical stability. There are crystallization temperature of PVA increasing, simultaneously at plasticizer content of 7,0 % of mass., and there is PP crystallization peak absent through polymer amorphization. There is crystallinity’s degree of PP decreases, through high dispersion state of polymer. Key words: polypropylene, poly(vinyl alcohol), melts of polymer blends, glycerol, microfibers, melting and crystallization.